Efficacy of Anti-IgE Therapy on Concurrent Upper and Lower Airway Outcomes in United Airway Disease: A Systematic Review and Meta-Analysis - Rinda; Dewi Wijaya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: United Airway Disease represents a paradigm wherein the upper and lower respiratory tracts function as a continuous immunological unit. Inflammatory conditions like allergic rhinitis, chronic rhinosinusitis with nasal polyps, and allergic asthma frequently co-occur, driven systemically by Type 2 inflammation and Immunoglobulin E. This study aimed to evaluate the concurrent efficacy of systemic anti-IgE therapy (omalizumab) on upper and lower airway outcomes in patients with United Airway Disease, addressing varying phenotypes and study designs. Methods: A systematic review and meta-analysis were conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The protocol was prospectively registered in PROSPERO. Data were extracted from nine primary studies. Standardized mean differences and risk ratios were pooled using a DerSimonian-Laird random-effects model with inverse variance weighting. To address methodological heterogeneity, a priori subgroup analyses stratified the data by study design (randomized controlled trials versus observational cohorts) and upper airway phenotype (allergic rhinitis versus chronic rhinosinusitis with nasal polyps). Publication bias was assessed via Egger’s regression test. Results: Nine studies comprising 1900 patients were included. Omalizumab significantly improved lower airway outcomes, with a pooled standardized mean difference of 1.45 (95% Confidence Interval: 1.12 to 1.78). Subgroup analysis revealed robust effects in both randomized trials and observational cohorts. Upper airway outcomes demonstrated profound symptom resolution (Standardized Mean Difference 1.32). Phenotypic stratification showed significant improvements in both allergic rhinitis and chronic rhinosinusitis with nasal polyps subgroups, though effect sizes varied slightly by local tissue remodeling profiles. The annualized rate of severe asthma exacerbations was reduced by a risk ratio of 0.48. Egger’s test indicated no significant publication bias (P = 0.15). Conclusion: Systemic anti-IgE therapy concurrently ameliorates upper and lower respiratory tract pathologies in United Airway Disease. These findings support the systemic use of biologics in patients who remain refractory to optimized standard-of-care topical therapies, aligning with stepwise clinical guidelines for severe disease management.